Ancient Egyptian Animal Fables : Tree Climbing Hippos and Ennobled Mice - Babcock, Jennifer Miyuki (Culture and History of the Ancient Near East, 2022)
One group of ancient Egyptian drawings has captured the curiosity of scholars and laypeople alike: images of animals acting like people. They illustrate animal fables originally from a larger mythological narrative, making them an integral part of New Kingdom Thebes's religious environment. This book examines the purpose of animal fables, drawing cross cultural and temporal comparisons to other storytelling and artistic traditions. This publication is also the first thorough art historical treatment of the ostraca and papyri. The drawings' iconography and aesthetic value are carefully examined, providing further nuance to our understanding of ancient Egyptian art.